ISOLATION AND IDENTIFICATION OF ENDOPHYTIC FUNGI FROM THE AMAZONIAN PALM Oenocarpus bataua MART - Viana diniz, Fernanda; Maria da Silva Rocha Doi, Songila; Cristina Pereira de Melo Fittipaldy, Márcia; de Freitas Lopes, Roberta; Sabrina Sondre de Oliveira Reis Margarido; Suelem Marina de Araújo Pontes; Dawerson da Paixão Ramos; Atilon Vasconcelos de Araújo; Clarice Maia Carvalho (South American Journal of Basic Education, Technical and Technological, 2021)
The aim of this study was to characterize the community of endophytic fungi of the Amazonian palm patauá Oenocarpus bataua in the state of Acre, Brazil. Samples of leaf and stem of O. bataua were collected, washed and disinfected by immersion in 70% ethanol (1 min), 2% sodium hypochlorite (5 min), 70% alcohol (30 sec) and washing in sterile distilled water (1 min) three times. The disinfected samples were fragmented and inoculated in PDA and Oat culture media and incubated at 28 ºC for 30 days. For identification, morphological characteristics of the colonies were observed. 63 endophytic fungi were isolated from O. bataua, 50 (79.3%) of leaf and 13 (20.7%) of stem. Regarding the culture medium, 24 (38.1%) fungi were isolated in BDA medium and 39 (61.9%) in Oat. Six genera were identified, Xylaria (33.3%), Phomopsis (12.6%), Phoma (4.8%), Geotrichum (4.8%), Penicillium (3.2%), Nigrospora (1.6%) and unidentified fungi (39.7%). This is the first report from the endophytic fungi community of O. bataua.